The GmCYCLOPS paralogs regulate soybean nodulation and exhibit signatures during domestication - Yuanting Lei; Zhi Liu; Qiang Chen; Xintong Wu; Ming Li; Fulong Liu; Yuzhen Liu; Zhitong Yin; Siyuan Zhao; Pengshuo Shen; Yuan Zhao; Sobhi F. Lamlom; et al. (Plant Science, 2026)

Inverse-opal g-C3N4-supported halogen-regulated Bi2WO6/Bi2SiO5/BiOClxBr1-x heterostructures for simulated-sunlight-driven antibiotic degradation - Jingyue Hu; Yuanting Wu; Mato Knez; Lihui Guo; Cuicui Wang; Hulin Liu; Xinmeng Zhang; Ou Hai; Yunlong Xue (Journal of Environmental Chemical Engineering, 2026)

The dietary flavonoid quercetin protects against visual cortical synaptic remodeling and ferroptosis in experimental myopia via the KEAP1-NRF2 pathway - Miao Zhang; Ruixue Zhang; Yuanting Yang; Xiaoyue Zhao; Baoyuan Sun; Zhongyu Ma; Mengke Wu; Jizhao Xin; Xuewei Yin; Hongsheng Bi; Dadong Guo (Food Bioscience, 2026)

Endoplasmic reticulum stress–based ATF6 signaling pathway: evaluation of 4-PBA improving retinal state in myopic guinea pigs - Mengke Wu; Miao Zhang; Mingbin Tian; Weibo Pan; Xuexin Wang; Ruixue Zhang; Yuanting Yang; Zhongyu Ma; Zhaohui Yang; Yinqiao Zhang; Hongsheng Bi; Dadong Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effect of oxygen vacancies induced by doping rare earth metal elements (La³⁺, Ce³⁺/⁴⁺, Nd³⁺) in NaTaO3 thin films on photocatalytic and antibacterial properties - Cuicui Wang; Shuxian Dong; Ruixue Yin; Anqi Cai; Haoyu Li; Zhizun Yue; Hongxia Ren; Chuanli Zhang; Hairong Yin; Yuanting Wu (Journal of Environmental Chemical Engineering, 2026)

Comparative analysis of nutritional and flavor compound alterations in Cordyceps militaris juice fermented by single or mixed Lactobacillus strains - Zeyang Li; Zhongxu Sun; Qingping Wu; Huiying Huang; Yuanting Tang; Jingwei Nan; Zhenjun Zhu; Yu Ding (Food Research International, 2025)

A 29-year-old male with eosinophilic myocarditis and multisystem involvement: A diagnostic dilemma between EGPA and idiopathic hypereosinophilic syndrome - Shan Ma; Yanqing Hu; Shuaiye Liu; Jihua Wang; Kun Zhang; Yuanting Zhu; Yang Wu (Next Research, 2025)

Mechanistic insights into ozone-induced asthma exacerbation: role of oxidative stress and IL-33 - Xinyi Fang; Bin Pan; Yuanting Xie; Wenpu Shao; Jingyu Li; Dongyang Han; Xiaoqing Hong; Wenyue Tu; Yifan Zhao; Jiaojiao Wu; Yaning Zhu; Yubin Zhang; et al. (Journal of Hazardous Materials, 2025)

Construction of inhomogeneous bismuth-based heterojunctions with efficient interfacial charge transport: Bridging of BiOX - Yuanting Wu; Lihui Guo; Xuhua Liu; Xiaoying Wang; Jingyue Hu; Yunlong Xue; Ou Hai; Hulin Liu; Xinmeng Zhang; Weizhi Tian; Yongqiang Feng (Environmental Research, 2025)

Differences in spatial pattern of expressway passenger and freight flows based on OTC data: A case study of Guangdong, China - Yuanjun Li; Yuanting Li; Qitao Wu; Zhuo Chen; Yunhao Yang (Applied Geography, 2025)

Construction of energy storage heterojunction and enhancement mechanism of dark and full-spectrum energy storage piezoelectric catalysis - Bixin Zhang; Guoqiang Tan; Wenlong Liu; Xiongtao Wu; Linxin Guo; Zeqiong Wang; Chunyan Zeng; Ying Liu; Tian Liu; Qian Yang; Ao Xia; Huijun Ren; et al. (Chemical Engineering Journal, 2025)

Characteristics of Higher Harmonic Forces on Submerged Horizontal Cylinders with Sharp and Round Corners - Hongfei Mao; Jinwen Zeng; Guanglin Wu; Hanqing Chen; Shuqin Zhang; Yuanting Yang; Qinru Yang (Journal of Marine Science and Engineering, 2024)
In this study, a two-phase flow numerical wave tank model based on the viscous flow theory was applied to conduct computational research on the interaction between waves and submerged horizontal cylinders. The research objective is to reveal the hydrodynamic characteristics of nonlinear loads on submerged horizontal cylinders with a focus on vortex effects. The influence of the sharp and round corners of cross-sections on the wave forces on cylinders was summarized. The reasons for the characteristics of the wave forces were explained by analyzing the flow field distribution around the cylinder and decomposing the wave forces into inertial and drag forces. This study found that under the various incident wave amplitudes, the section corner and aspect ratio have significant impacts on each frequency component of the horizontal and vertical wave forces. The distribution of the vorticity field shows that the vortex effects lead to the differences between the loads on the cylinder under different cross-sectional corners and aspect ratios. The characteristics of inertial forces and drag forces on the cylinders were given by comparing and analyzing the cases with different sectional sharp and round corners. The inertia and drag coefficients were obtained by solving Morison’s equation. Under various Kc and Re numbers, the maximum values of the inertia and drag coefficients obtained are significantly different from those for submerged cylinders under oscillatory flow action.

Promotion of manganese on Fe-based catalyst for the production of carbon nanotubes (CNTs) from plastics - Su He; Chunchun Li; Hongman Sun; Christopher M.A. Parlett; Yuanting Qiao; Youhe Wang; Yikai Xu; Ningbo Gao; Chunfei Wu (Chemical Engineering Journal, 2024)

Sequence and epigenetic variations of R2R3-MYB transcription factors determine the diversity of taproot skin and flesh colors in different cultivated types of radish (Raphanus sativus L.) - Qingbiao Wang; Yanping Wang; Xiangyu Wu; Wenyu Shi; Ningjie Chen; Yuanting Pang; Li Zhang (Theoretical and Applied Genetics, 2024)

A NAC Transcription Factor RsSND1 Regulating Secondary Cell Wall Deposition Involves in Fleshy Taproot Formation in Radish (Raphanus sativus L.) - Yanping Wang; Qingbiao Wang; Xiangyu Wu; Yuanting Pang; Yu Guo; Zixiong Li; Li Zhang (Journal of Plant Growth Regulation, 2024)

Estimation of expressway carbon emissions and simulation of policies based on OTC data: A case study of Guangdong, China - Yuanjun Li; Qitao Wu; Yuanting Li; Yunhao Yang; Hailing Wu; Yong Sun (Urban Climate, 2024)

Machine-learning-assisted hydrogen adsorption descriptor design for bilayer MXenes - Weizhi Tian; Gongchang Ren; Yuanting Wu; Sen Lu; Yuan Huan; Tiren Peng; Peng Liu; Jiangong Sun; Hui Su; Hong Cui (Journal of Cleaner Production, 2024)

Azobenzene-equipped Covalent triazine polymers for Visible-Light-Driven photocatalytic reduction of CO2 to CH4 - Qi Huang; Zhen Zhan; Yuanting Qiao; Xueting Pan; Shaojun Xu; Bien Tan; Chunfei Wu (Fuel, 2024)

Techno-economic analysis of integrated carbon capture and utilisation compared with carbon capture and utilisation with syngas production - Yuanting Qiao; Weishan Liu; Ruonan Guo; Shuzhuang Sun; Shuming Zhang; Josh J. Bailey; Mengxiang Fang; Chunfei Wu (Fuel, 2023)

The monthly variation tendency of microcystin-LR levels in the Huangpu River (China) by applications of ELISA and HPLC - Sijia Hua; Jiawen Chen; Liang Wu; Xinyue Yu; Jing Ye; Yuanting Li; Yongqiang Zhu; Fuxiang Tian (Environmental Science and Pollution Research, 2022)

Activation of the bitter taste sensor TRPM5 prevents high salt-induced cardiovascular dysfunction - Hao Wu; Yuanting Cui; Chengkang He; Peng Gao; Qiang Li; Hexuan Zhang; Yanli Jiang; Yingru Hu; Xiao Wei; Zongshi Lu; Tianyi Ma; Daoyan Liu; et al. (Science China Life Sciences, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.